(untitled) - Hale, J. R. (Berkeley, 1972)
This book is planned on somewhat different lines from companions in history of Europe series. While not irnorring the events on which a sense of chronology depends, it aims chiefly at providing a means of understanding the quality.
Keywords: Renaissance,Europe,Thời phục hưng,Châu Âu; History,Lịch sử; 1492-1517,1492-1517